P02.09 Integrated single-cell profiling dissects cell-state-specific enhancer landscapes of human tumor-infiltrating T cells. (21st September 2022) - Schmidl, C; Riegel, D; Romero-Fernández, E; Simon, M; Adenugba, A; Singer, K; Mayr, R; Weber, F; Imbusch, CD; Kreutz, M; Brors, B; Ugele, I; et al.
Abstract : Background: Despite extensive studies on the chromatin landscape of exhausted T cells, the transcriptional wiring underlying the heterogeneous functional and dysfunctional states of human tumor-infiltrating lymphocytes (TILs) is incompletely understood. Materials and Methods: We use single-cell chromatin profiling and integrate publicly available single-cell RNA-seq data of TILs from several patients over four cancer entities to study gene-regulation in T cell (dys-)function. Results: We identify gene-regulatory landscapes in a wide breadth of CD8 + TIL functional states. Our analysis predicts enhancer-promoter interactions in human TILs and prioritizes key elements by super-enhancer analysis. We define a human common chromatin trajectory to T cell dysfunction and determine involved key enhancers, transcriptional regulators, and deregulated target genes in this process. Finally, we validate enhancer regulation at immunotherapeutically relevant loci by targeting non-coding regulatory elements with potent CRISPR activators and repressors. Conclusions: Our study provides a framework for understanding and manipulating cell-state-specific gene-regulatory cues from human tumor-infiltrating lymphocytes. Disclosure Information: C. Schmidl: None. D. Riegel: None. E. Romero-Fernández: None. M. Simon: None. A. Adenugba: None. K. Singer: None. R. Mayr: None. F. Weber: None. C.D. Imbusch: None. M. Kreutz: None. B. Brors: None. I. Ugele: None. J.M. Werner: None. P.J. Siska: None.